(untitled) (EAAE Annual Conference Proceedings, 2023)
Architecture that evolves with the landscape -both natural and culturalis a call to re-examine today’s realities within the framework of climate change, limited resources and an unprecedented flow of migration around the globe; furthermore, landscape is an important constituent of place making along the European South, where well-being and a sense of freedom stem from the moderate climate and the prolonged life outdoors. Natural environment, local materials and landscape are also discussed as the treasures of the Southern European cultural continuum where inherent values of heritage and anonymous architecture are preserved. Landscape is investigated in its multitude and intrinsic nature, as imaginary locus, mindscape and landform.